The Influence of Human Resource Development and Leadership on Employee Performance with Work Commitment as a Mediation (Pusat Riset dan Inovasi Nasional, 2026)
Frentho Valentino Efrath Reinati (Master of Management, Universitas Widya Gama Malang, 2025) entitled